THE AMBIGUITY OF IDENTITY, "IN OTHER ROOMS, OTHER WONDERS" BY DANIYAL MUEENUDDIN - Hafsa Jafar (International Journal of Contemporary Issues in Social Sciences, 2024)
In Daniyal Mueenuddin's "In Other Rooms, Other Wonders," an elaborate system of interconnected stories. It explores the complexities of one's self within Pakistan's ancient system. The book explores the lives of people from various walks of life. He emphasizes the dynamic relationship between social standing, political strength, and private destiny. Mueenuddin's story provides an engaging picture of Pakistani culture and obligations to family and society. Mueenuddin raises major questions about the definition of being one itself. Whether it is a fundamental concept. Through his in-depth portrayal of common challenges and successes, he reveals a natural characteristic or an outcome of external forces. He highlights how skillfully the writer conveys the multifaceted nature of human feeling. The complicated nature of relationships built and broken in the background of greater societal demands. "In Other Rooms, Other Wonders" encourages readers to think about the common problems of life. Such as love, sorrow, and the search for identity in the complexity of humanity. Providing insight into Pakistani culture.